Syysseminaarin satoa. Ideoita koulutusyhteistyöhön ja käännösteknologian opetukseen - Leena Salmi; Maarit Koponen; Turo Rautaoja; Outi Veivo (My University, 2022)
This article reports on the autumn seminar of the Teachers' and Researchers' Section of the Finnish Association of Translators and Interpreters, held at the University of Turku in August 2017. The theme of the seminar was cooperation and technology teaching, which was addressed in two presentations as well as learning café discussions together with the participants. In this article, we summarize the presentations and report ideas for cooperation that emerged in the learning café discussions.